COMPARISON OF SOXHLETATION EXTRACTION METHODS AND UAE ON ANTIFUNGAL ACTIVITIES Candida albicans ON COCOA BEAN EXTRACT (Theobroma cacao L.) - Novi Purwaningtyas (LPPM Universitas dr. Soebandi, 2024)
Chocolate beans (Theobroma cacao L.) is the main part of the chocolate fruit and can be consumed after it becomes a food or beverage product. Cocoa beans contain quite high levels of active antioxidant compounds, some of which are 33-42% catechins, 23-25% leukocyanidins, and 5% anthocyanins. One of the bioactive compounds that are efficacious as natural antioxidants and antimicrobials is polyphenols. This study aims to determine the comparison of soxhletation and UAE extraction methods on antifungal activity Candida albicans on cocoa bean extract. The research design is an experimental laboratory. Processed using the soxhletation and UAE extraction methods with methanol as a solvent, then a phytochemical screening was carried out to determine the chemical compound content in cocoa beans and an antifungal test was carried out on Candida albicans by hole cup diffusion method with a concentration of 50%. The results showed that the yield values ​​of the soxhletation and UAE method were 3.81 ± 0.0022 and 4.18 ± 0.0012. Methanol extract of cocoa beans by soxhletation method and UAE contains chemical compounds of alkaloids, flavonoids, saponins, tannins and polyphenols. The results of the antifungal test by the soxhletation and UAE methods with a concentration of 50% produced an average inhibition zone diameter of 5.44 ± 0.5652 mm and 6.60 ± 0.6372 mm. It can be concluded that the extraction method does not affect the content of chemical compounds in cocoa beans and has an effect on antifungal activityCandida albicans which was indicated by the diameter of the inhibition zone but did not show a significant difference.